Validation of MyFORTA: an automated tool to improve medications in older people based on the FORTA list - Wehling, Martin; Weindrich, Johannes; Weiß, Christel; Heser, Kathrin; Pabst, Alexander; Luppa, Melanie; Bickel, Horst; Weyerer, Siegfried; Pentzek, Michael; König, Hans-Helmut; Lühmann, Dagmar; van der Leeden, Carolin; et al. (Drugs & aging, 2024)
Listing tools have been developed to improve medications in older patients, including the Fit fOR The Aged (FORTA) list, a clinically validated, positive-negative list of medication appropriateness. Here, we aim to validate MyFORTA, an automated tool for individualized application of the FORTA list.
Gesehen am 02.12.2024